2022
DOI: 10.2337/db22-739-p
|View full text |Cite
|
Sign up to set email alerts
|

739-P: iGlarLixi vs. Premixed Insulin Initiation in Adults with Type 2 Diabetes (T2D) Advancing from Basal Insulin (BI) Therapy: SoliComplex Real-World Study

Abstract: Aim: Premixed insulin (premix) , conventionally administered twice daily, is often used in the US to treat T2D that is suboptimally controlled with BI, particularly for people with consistent eating patterns who require affordable treatment. This analysis evaluated use of once daily iGlarLixi vs. premix on T2D outcomes. Method: This retrospective analysis of the US Optum Clinformatics database compared outcomes in adults (≥18 y) with T2D who previously received BI and newly initiated iGlarLixi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…when comparing iGlarLixi with a free-dose combination of basal insulin and GLP-1 RA, as well as in comparisons of iGlarLixi with a basal plus prandial insulin, and with premix insulin. [24][25][26] One of the strengths of this study is that the PRO measures capture participant perspectives on diabetes treatment that are not provided by clinical trial outcomes. The multinational design is also a strength of the SoliMix study as it allows assessment of PRO data In conclusion, alongside the previously reported better glycaemic control, weight benefit and less hypoglycaemia, 10 once-daily iGlarLixi provided better PROs compared with twice-daily premix BIAsp 30 in people with suboptimally controlled T2D on basal insulin plus OADs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…when comparing iGlarLixi with a free-dose combination of basal insulin and GLP-1 RA, as well as in comparisons of iGlarLixi with a basal plus prandial insulin, and with premix insulin. [24][25][26] One of the strengths of this study is that the PRO measures capture participant perspectives on diabetes treatment that are not provided by clinical trial outcomes. The multinational design is also a strength of the SoliMix study as it allows assessment of PRO data In conclusion, alongside the previously reported better glycaemic control, weight benefit and less hypoglycaemia, 10 once-daily iGlarLixi provided better PROs compared with twice-daily premix BIAsp 30 in people with suboptimally controlled T2D on basal insulin plus OADs.…”
Section: Discussionmentioning
confidence: 99%
“…Once‐daily treatment with iGlarLixi offers a simpler, more convenient treatment regimen that is less burdensome compared with twice‐daily BIAsp 30 and therefore may potentially encourage better real‐world treatment adherence and persistence. Indeed, improved adherence and persistence with treatment and a lower risk of treatment discontinuation have been observed when comparing iGlarLixi with a free‐dose combination of basal insulin and GLP‐1 RA, as well as in comparisons of iGlarLixi with a basal plus prandial insulin, and with premix insulin 24‐26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, patient-reported outcomes (including the Treatment-Related Impact Measure Diabetes) indicated a preference for iGlarLixi over BIAsp 30 in the SoliMix trial [14]. This assumption is further supported by the higher persistence with iGlarLixi compared with basal insulin and premixed insulins demonstrated in the SoliComplex real-world study [26,27].…”
Section: Discussionmentioning
confidence: 76%
“…The SoliComplex observational RWE study in people with T2D advancing their therapy from BI showed that GlarLixi was associated with higher treatment persistence, alongside similar HbA1c reductions compared with premixed and basal‐bolus insulin regimens. 15 , 16 Another major factor leading to non‐compliance with insulin‐based treatments is the fear of weight gain. 17 As iGlarLixi is associated with less weight gain compared with premixed insulin, it could be a suitable option.…”
Section: Discussionmentioning
confidence: 99%